Determination of service quality and marketing mix to customer loyalty with customer satisfaction as intervening variables - Sambodo Rio Sasongko; Amir Tengku Ramly; Kurnia Endah Riana (Insight Management Journal, 2026)
This study aims to empirically examine the effect of service quality (SERVQUAL-based) and marketing mix (4C approach) on customer loyalty with customer satisfaction as a mediating variable in the building materials retail industry in the Jabodetabek area. Using a quantitative approach with an inferential descriptive design, data were collected through an online questionnaire from 435 respondents of Depo Bangunan and Mitra10 selected using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a second-order construct approach. The results show that service quality and marketing mix have a positive and significant effect on both customer satisfaction and loyalty, with the marketing mix being the most dominant predictor. Furthermore, customer satisfaction is proven to significantly act as a partial mediating variable bridging the relationship between service quality and marketing mix on loyalty. As a practical recommendation, building materials retail management is advised to improve staff technical competencies, optimize transaction efficiency, and design after-sales guarantees and loyalty incentive programs. Future researchers are recommended to add variables such as perceived value or customer experience and expand the sample scope using mixed methods.